2016
DOI: 10.1002/cbdv.201500101
|View full text |Cite
|
Sign up to set email alerts
|

New Caledonia: A Hot Spot for Valuable Chemodiversity Part 3: Santalales, Caryophyllales, and Asterids

Abstract: The flora of New Caledonia encompasses more than 3000 plant species and an endemism of almost 80%. New Caledonia is even considered as one of the 34 'hot spots' for biodiversity. Considering the current global loss of biodiversity and the fact that several drugs and pesticides become obsolete, there is an urgent need to increase sampling and research on new natural products. In this context, here, we reviewed the chemical knowledge available on New Caledonian native flora from economical perspectives. We expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Out of the 22 iridoids so far isolated from P. subcordata, (21) is observed to be the most common and widely distributed iridoid of the species; it was isolated as the major component of the methanol extract of dry fruits and stem bark of P. subcordata . Another species that yielded iridoids is P. odorata ; its leaf and bark produced four glycosidic iridoids (23–26) , in company with other non-iridoid constituents (Coulerie and Poullain 2016 ; Sévenet and Pusset 1996 ). These data on iridoids suggest that the genus accumulates high amounts of this class of metabolites which may be of taxonomic relevance in plant systematics if further investigation is carried out.…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 22 iridoids so far isolated from P. subcordata, (21) is observed to be the most common and widely distributed iridoid of the species; it was isolated as the major component of the methanol extract of dry fruits and stem bark of P. subcordata . Another species that yielded iridoids is P. odorata ; its leaf and bark produced four glycosidic iridoids (23–26) , in company with other non-iridoid constituents (Coulerie and Poullain 2016 ; Sévenet and Pusset 1996 ). These data on iridoids suggest that the genus accumulates high amounts of this class of metabolites which may be of taxonomic relevance in plant systematics if further investigation is carried out.…”
Section: Phytochemistrymentioning
confidence: 99%
“…On the contrary, some other research groups identified alkaloids in a different part of P. subcordata, P. horizontalis, P. schimperiana and P. dicoccos , but they reported the alkaloid content of P. schimperiana and P. dicoccos to be small (Anokwah et al 2016 ; Feenna et al 2020 ; Ochwang’i et al 2016 ; Umaiyambigai et al 2016 ). To confirm the presence of alkaloids in Psydrax , three alkaloids: two monoterpene alkaloids (40 and 41) and a peptide alkaloid (42) were isolated from P. odorata bark and leaf (Coulerie and Poullain 2016 ) and their structures are given in Fig. 4 .…”
Section: Phytochemistrymentioning
confidence: 99%
“…source of bioactive compounds, and more than 80 antibacterial drugs deriving from NPs were approved by the FDA between 1981 and 2014 (Newman & Cragg, 2016). New Caledonia is considered as a major "hot spot" for terrestrial biodiversity with 3,200 native species and 78% of endemism representing a valuable source of bioactive NPs (Coulerie & Poullain, 2016). Xylopia pancheri Baill.…”
mentioning
confidence: 99%
“…(Annonaceae) is an endemic shrub that grows on peridotite ground of New Caledonia (Johnson, Munzinger, Peterson, & Murray, 2013;Morat et al, 2012;Munzinger et al, 2016;Turner & Utteridge, 2017), and, to the best of our knowledge, only one study has characterized the chemical composition of the plant leaves and bark extracts and none of their biological activities (Niéto, Sévenet, Leboeuf, & Cavé, 1976). Total leaf extract and alkaloid fraction of X. pancheri were shown to exert light peripheral vasodilatory activity in mice but no experimental demonstration was presented (Coulerie & Poullain, 2016;Sévenet & Pusset, 1996). Herein, we investigated the antibacterial activities of X. pancheri leaf extracts (XPLEs) against (i) susceptible S. aureus and MRSA, and (ii) extended-spectrum-β-lactamase (ESBL)-producing Pseudomonas aeruginosa.…”
mentioning
confidence: 99%